Which uncertainty measures matter for corporate financialization? Evidence from China intensive polluted industries - Wang, Mingyao; Mohd Nor, Normaziah; Abdul Rahim, Norhuda; Khan, Faisal; Cheng, Yuxiang (Cogent OA, 2025)
Corporate financialization in intensively polluting industries has become a critical factor in understanding the intersection of financial behaviour and sustainable development. This study investigates which specific forms of uncertainty including economic policy, monetary policy, trade policy, and oil price uncertainty can significantly influence financialization within China’s intensively polluting sectors. Utilizing a panel dataset of Chinese A-share listed companies from 2011Q1 to 2022Q4, this study applies Principal Component Analysis (PCA) to construct a multidimensional index of financialization, followed by panel regression analysis. Findings reveal that global economic policy uncertainty exerts the most significant impact on corporate financialization in these industries. Furthermore, financing constraints negatively moderate this relationship, while Environmental, Social, and Governance (ESG) practices have positive moderating effects. Firms with higher managerial overconfidence exhibit increased levels of financialization. Additionally, heterogeneity exists across firms, with those incurring higher environmental protection fees, non-state-owned enterprises, and firms based in developed eastern regions displaying elevated financialization levels. Diversification and external monitoring also positively influence this relationship. Robustness tests confirm the consistency of these findings, providing valuable insights for firms seeking to strategically leverage ESG, financial technology (FinTech), and financialization practices in response to fluctuating uncertainties.